The Effect of Carrageenan and Konjac Proportion as Gelling Agents on the Physicochemical Characteristics and Hedonic Value of Arum Manis Mango Jelly Drink - Siti Susanti; Hafidhi Izzati; Bhakti Etza Setiani; Hega Bintang Pratama Putra; Maela Rizky Kusumastuti (Universitas Ahmad Dahlan, 2026)
This study investigated the effect of carrageenan and konjac ratios as gelling agents on the physicochemical and sensory properties of Arumanis mango (Mangifera indica L.) jelly drink. Jelly drinks are increasingly popular functional beverages, but their texture and stability depend heavily on the gelling system applied. Carrageenan forms strong gel networks but is prone to syneresis, whereas konjac glucomannan improves viscosity and elasticity. Their combination is contributed to produce a stable and consumer-acceptable jelly drink. Four gelling agent ratios (100:0, 80:20, 60:40, and 40:60 carrageenan-to-konjac) were prepared in a Completely Randomized Design (CRD) with five replications. Parameters measured included moisture content, pH, syneresis, viscosity, and hedonic acceptance by 25 semi-trained panelists. Results showed that increasing konjac proportion significantly decreased moisture content (90.99–90.05%) and syneresis (27.87–14.59%), while enhancing viscosity (194.50–321.50 cP). The pH decreased with higher konjac levels (5.50–5.22) due to the presence of organic acids in mango interacting with konjac glucomannan. Sensory evaluation revealed that texture was significantly affected, with the 60:40 carrageenan-to-konjac ratio (P2) achieving the highest acceptance for chewiness and ease of sipping. Color, taste, and aroma showed no significant differences across treatments, although mango aroma dominated the product profile. Overall, the combination of carrageenan and konjac demonstrated a synergistic effect in improving stability and consumer preference. The 60:40 ratio was identified as the most favorable formulation. This research contributes to the development of functional jelly drinks based on tropical fruits.